(untitled) (International Journal of Food and Nutritional Sciences, 2019)
Electronic waste (e-waste) has emerged as a pressing global concern due to the rapid proliferation of electronic devices and the challenges associated with their disposal. The inadequate handling of e-waste poses significant environmental and health risks. To address this issue, the integration of Information Technology (IT) into e-scrap dismantle systems offers a promising avenue for achieving greater efficiency, resource recovery, and environmental sustainability. This research paper explores the diverse applications of IT in the realm of e-waste dismantling, encompassing inventory management, automated sorting, data analytics, and environmental monitoring. It discusses the challenges associated with technological implementation, data privacy, and e-waste heterogeneity. Moreover, the paper highlights the substantial benefits of such IT-driven solutions, including enhanced resource efficiency, conservation efforts, and the promotion of circular economy principles. As technology continues to evolve, the potential for more advanced IT applications in e-scrap dismantling is on the horizon, underscoring the importance of this research field in addressing the complex challenges of electronic waste management.